Biased M1-muscarinic-receptor-mutant mice inform the design of next-generation drugs - Bradley, Sophie J.; Molloy, Colin; Valuskova, Paulina; Dwomoh, Louis; Scarpa, Miriam; Rossi, Mario; Finlayson, Lisa; Svensson, Kjell A.; Chernet, Eyassu; Barth, Vanessa N.; Gherbi, Karolina; Sykes, David A.; et al. (Nature chemical biology, 2020)
Cholinesterase inhibitors, the current frontline symptomatic treatment for Alzheimer’s disease (AD), are associated with low efficacy and adverse effects. M1 muscarinic acetylcholine receptors (M1 mAChRs) represent a potential alternate therapeutic target; however, drug discovery programs focused on this G protein-coupled receptor (GPCR) have failed, largely due to cholinergic adverse responses. Employing novel chemogenetic and phosphorylation-deficient, G protein-biased, mouse models, paired with a toolbox of probe molecules, we establish previously unappreciated pharmacologically targetable M1 mAChR neurological processes, including anxiety-like behaviors and hyper-locomotion. By mapping the upstream signaling pathways regulating these responses, we determine the importance of receptor phosphorylation-dependent signaling in driving clinically relevant outcomes and in controlling adverse effects including ‘epileptic-like’ seizures. We conclude that M1 mAChR ligands that promote receptor phosphorylation-dependent signaling would protect against cholinergic adverse effects in addition to driving beneficial responses such as learning and memory and anxiolytic behavior relevant for the treatment of AD. Use of receptor variants in knock-in mice to dissect phosphorylation-dependent signaling from G protein-dependent signaling mediated by acetylcholine receptor M1 mAChR defines the ability of receptor ligands to modulate anxiety and locomotion behaviors.